Contribution of extracellular solute transfer to testicular cell damage - O. V. Pakhomov; E. I. Legach; O. S. Protsenko; N. A. Chernobai; G. A. Bozhok (Regulatory Mechanisms in Biosystems, 2024)
Cryopreservation of cells involves many mechanisms of cell damage. The main general mechanisms are immediate cell damage by growing intracellular ice crystals and the adverse influence of hyperconcentrated solutions on cellular components. The formation of the solutions is triggered by intra- and extracellular ice growth. Components of the hyperconcentrated solution may enter living cells during cooling and lead to the post-hypertonic lysis of the cells on warming of the cells and on removal of cryoprotective agents. The mechanisms of entry of extracellular solutes such as Na+ and Cl– ions is unclear. Some studies believe that they may involve the opening of mechanosensitive ion channels when cellular membranes are stretched or squeezed. The present work has assessed the involvement of the mechanisms of ion transport across the membrane of rat testis interstitial cells in their post-hypertonic lysis and its contribution into the interstitial cell loss after incubation and cryopreservation. It has been shown that incubation in anisosmotic conditions with and without dimethyl sulfoxide lowered the indicators of interstitial cell survival. Furthermore, the gradual removal of hyperconcentrated media increased the survival of interstitial cells, which points to the osmotic mechanisms of interstitial cell damage. The mechanisms would be caused by the initial entry of inorganic ions or cryoprotective agent dimethyl sulfoxide (DMSO) into the cells. However, the use of the inhibitor of ion transport across the membrane chlorpromazine did not improve the survival of interstitial cells after incubation. DMSO, able to suppress ion transfer across the membrane, lowered the survival of cells. Interestingly, this lowering effect was less pronounced at moderately hypertonic medium (600 mOsm). Chlorpromazine did not improve the outcome of cryopreservation with 0.7 M DMSO. Thus, the contribution of the entry of inorganic solutes into the post-hypertonic IC damage was minimal after incubation, although, gradual removal of DMSO or transfer of the interstitial cells into isosmotic condition is justified. Chlorpromazine did not provide any advantages for cryopreservation of interstitial cells.